A giant angiomyolipoma arising from the hepatic round ligament: a case report and literature review - Zheng, Hai-Bo; Wang, Xiang-Qian; Liu, Xian-Ni; Han, Xiu-Min; Zhu, Hai-Hong (Frontiers in Oncology, 2025)
Angiomyolipoma (AML) is a type of tumor of mesenchymal origin that is most commonly found in the kidney, although it has been found in the liver in rare cases. Herein, we document the first known instance of an AML identified within the liver’s round ligament. A 22-year-old woman presented with a 41-month history of a painless abdominal mass that gradually enlarged. She was misdiagnosed with primary hepatic carcinoma 34 months prior at another hospital and received transcatheter arterial chemoembolization (TACE). After failure of TACE, computed tomography (CT) indicated possible malignant neoplasms. In our hospital, an abdominal CT scan revealed a large mass occupying the right hypochondrium but no evidence of metastatic disease. Consequently, the decision was made to proceed with surgery. During laparotomy, a large, well-defined tumor was discovered, which, surprisingly, was attached to the liver’s round ligament and isolated from any other intra-abdominal structures. The tumor was excised with ease, and monobloc resection and macroscopically total removal were achieved. Histopathological examination confirmed that the tumor was an AML originating from the liver’s round ligament. Postoperative care did not include adjuvant therapy. The patient remains alive and free from any indications or symptoms of recurrence 46 months postsurgery. This case represents the first documented instance of an AML developing from the liver’s round ligament and underscores the diagnostic challenges posed by such tumors. Although uncommon, AML diagnoses should be considered to facilitate early detection and complete surgical excision, which are pivotal for optimal patient outcomes.